2012
DOI: 10.1016/j.jcv.2011.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Sequential changes in pathophysiology of systemic inflammatory response in a disseminated neonatal herpes simplex virus (HSV) infection

Abstract: 1 Background. Disseminated neonatal herpes simplex virus (HSV) infection causes a typical2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Dysregulated secretion of pro-inflammatory cytokines in response to HSV infection also induces the production of high mobility group box 1 protein (HMGB1) from injured cells ( 158 ). HMGB1 is a nuclear protein and regulates DNA transcription.…”
Section: The Immunology Of Viral Sepsismentioning
confidence: 99%
“…Dysregulated secretion of pro-inflammatory cytokines in response to HSV infection also induces the production of high mobility group box 1 protein (HMGB1) from injured cells ( 158 ). HMGB1 is a nuclear protein and regulates DNA transcription.…”
Section: The Immunology Of Viral Sepsismentioning
confidence: 99%
“…They used methylprednisolone within 72 hours after the disease onset and suggested that methylprednisolone therapy might be effective for the control of neonatal disseminated HSV infection with HLH. Nagamori et al (2012) reported a successfully treated case of neonatal disseminated HSV infection with early anti-inflammatory therapy using prednisolone and concluded that anti-inflammatory intervention might only be effective if it is undertaken during the early phase. In our case, 6 days were passed from disease onset before using methylprednisolone.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal disseminated infections with HSV-1 or HSV-2 led to SIRS represented by high IL-6 and TNF-α levels, and occasionally to the rapid demise of multiple organ dysfunction syndrome or HLH. 9 10 11 12 Methylprednisolone therapy might be effective for the control of neonatal disseminated HSV infection with HLH. 10 11 In this reported case, 10 sequential changes in the declining pattern of IL-6, IL-10, and IFN-γ levels were consistent with the results of our observation, although HSV DNA copy number was not monitored.…”
Section: Discussionmentioning
confidence: 99%
“… 9 10 11 12 Methylprednisolone therapy might be effective for the control of neonatal disseminated HSV infection with HLH. 10 11 In this reported case, 10 sequential changes in the declining pattern of IL-6, IL-10, and IFN-γ levels were consistent with the results of our observation, although HSV DNA copy number was not monitored. On the contrary, appreciable levels of IL-10 and IFN-γ in the neonates with virus-associated HLH might be associated with a good prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation